2019
DOI: 10.3201/eid2508.190059
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Novel Recombinant Norovirus GII.P16-GII.12 Strain Causing Gastroenteritis, Alberta, Canada

Abstract: We identified a novel recombinant GII.P16-GII.12 norovirus associated with epidemic and endemic gastroenteritis during March 1, 2018–February 12, 2019, in Alberta, Canada. GII.12 viruses have not been detected in Alberta since 2000. Comparing the full genome of this strain to previously published sequences revealed this virus to be a novel recombinant strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Notably, the emergence of a novel GII.P16 ORF1 allele has been linked to multiple new recombinant strains circulating worldwide (e.g. GII.4[P16], GII.2[P16]; GII.12[P16]) 5,9‐13 . Although theoretically over 1200 different capsid‐polymerase type combinations are possible, large genome studies showed that only a fraction of those combinations seem to be viable and persist in nature 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the emergence of a novel GII.P16 ORF1 allele has been linked to multiple new recombinant strains circulating worldwide (e.g. GII.4[P16], GII.2[P16]; GII.12[P16]) 5,9‐13 . Although theoretically over 1200 different capsid‐polymerase type combinations are possible, large genome studies showed that only a fraction of those combinations seem to be viable and persist in nature 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A novel recombinant norovirus GII.12[P16] genotype, which was never reported from Bangladesh, was detected in both populations. This novel strain was associated with epidemic and endemic gastroenteritis in hospital settings in Alberta, Canada, during the 2018–2019 season [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant GII.12[P16] was first identified in the United States in 2017 ( Barclay et al., 2019 ). The endemic circulation of this recombinant variant was reported in the United States and Canada 2017-2018 ( Pabbaraju et al., 2019 ). The whole-genome sequence analysis showed the GII.12[P16] identified in Guangdong 2021 was clustered with the previous strains identified in the United States and Canada, sharing 96.99% sequence similarity to the closely related strain (MK762627, Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is the first identification of the recombinant GII.12[P16] in mainland China following the large outbreaks caused by the recombinant GII.17[P17] and GII.2[P16] in 2014 and 2016 ( Lu et al., 2015 , n.d.), respectively. This variant was suggested to be endemically circulating in the United States in 2017 and Canada in 2018, but has not been identified in other regions ( Barclay et al., 2019 ; Pabbaraju et al., 2019 ). Our results highlighted the epidemic risk of this emerging variants, and the divergence between the Guangdong strains and the relative strains identified in the U.S. and Canada indicating the hidden circulation of this variant in the population.…”
Section: Discussionmentioning
confidence: 99%